Law and Regulation as Safeguards for Investors Against Crime in Capital Market Sector - Chamdani; Indradjaja, Nobella; Wijaya, Sonny (Neoclassical Legal Review: Journal of Law and Contemporary Issues, 2024)
As a country with potency in economic growth, Indonesia is supported by several essential sectors, and one of them is through the Capital Market. The capital market enables the growth acceleration for a company or country by providing the needed fund. At least, through this medium, there are reciprocal benefits obtained by both parties involved in the Capital Market: issuers with capital injections, and investors with dividends and price increases. Unfortunately, there are big risks that investors have to deal with in capital markets, and some of them are related to fraud, market manipulation and insider trading. The results of this research found that government has enacted regulations that protect investors' rights through the Capital Market Law and the Financial Services Authority Law. However, there are still weaknesses in this regulation, especially for types of crimes that are still not regulated in this regulation. Moreover, it is necessary to have sufficient prowess from the authorized institution, especially Â the Financial Services Authority (OJK), to resolve cases in accordance with the applicable law aiming to protect investors' rights.